MEMBANGUN KEBIASAAN AKTIF BERGERAK MELALUI KEGIATAN SIT LESS MOVE MORE PADA PENDERITA OBESITAS - Iswati Iswati; Alfian Irdhani Mohammad; Putri Sukma Rahayu (PPM STIKES Adi Husada, 2026)
Introduction & Objective: A sedentary lifestyle (lack of movement, lots of sitting/lying down) can increase the risk of heart disease, diabetes, and obesity. Obesity is a global health problem that requires sustainable interventions. This activity aims to build active movement habits in individuals with obesity through the implementation of the